2013
DOI: 10.1007/s13318-013-0133-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mirabegron, a potent and selective β3-adrenoceptor agonist, on the pharmacokinetics of CYP2D6 substrates desipramine and metoprolol

Abstract: Mirabegron is a potent and selective β3-adrenoceptor agonist developed for the treatment of overactive bladder. In vitro studies demonstrated that mirabegron partly acts as a (quasi-) irreversible, metabolism-dependent inhibitor of CYP2D6. The effect of steady-state mirabegron on single doses of the sensitive CYP2D6 substrates metoprolol (100 mg) and desipramine (50 mg) was assessed in two open-label, one-sequence crossover studies in healthy subjects (CYP2D6 extensive metabolizers). Mirabegron 160 mg/day incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…21 A study with metoprolol and mirabegron showed that the combination of multiple doses of mirabegron 160mg/day and a single dose of metoprolol 100mg/day showed an increase in the area under the curve (AUC) of metoprolol by 3.29 fold and mean increase in half-life from 2.96 hours to 4.11 hours. 29 Similar to metoprolol, there was a 3.41 fold increase in AUC of desipramine and mean increase in half-life from 19.5 hours to 35.8 hours after a 50mg single dose of desipramine was administered to patients having taken multiple doses of mirabegron 100mg/day. 29 Monitoring should also be employed with CYP2D6 substrates with narrow therapeutic indices such as thioridazine, flecainide, and propafenone.…”
Section: Drug Interactionsmentioning
confidence: 92%
See 1 more Smart Citation
“…21 A study with metoprolol and mirabegron showed that the combination of multiple doses of mirabegron 160mg/day and a single dose of metoprolol 100mg/day showed an increase in the area under the curve (AUC) of metoprolol by 3.29 fold and mean increase in half-life from 2.96 hours to 4.11 hours. 29 Similar to metoprolol, there was a 3.41 fold increase in AUC of desipramine and mean increase in half-life from 19.5 hours to 35.8 hours after a 50mg single dose of desipramine was administered to patients having taken multiple doses of mirabegron 100mg/day. 29 Monitoring should also be employed with CYP2D6 substrates with narrow therapeutic indices such as thioridazine, flecainide, and propafenone.…”
Section: Drug Interactionsmentioning
confidence: 92%
“…29 Similar to metoprolol, there was a 3.41 fold increase in AUC of desipramine and mean increase in half-life from 19.5 hours to 35.8 hours after a 50mg single dose of desipramine was administered to patients having taken multiple doses of mirabegron 100mg/day. 29 Monitoring should also be employed with CYP2D6 substrates with narrow therapeutic indices such as thioridazine, flecainide, and propafenone. A dose adjustment is recommended when initiating digoxin with mirabegron.…”
Section: Drug Interactionsmentioning
confidence: 92%
“…The first was a phase 1 study assessing mirabegron pharmacokinetics after multiple doses (50 or 100 mg) over a period of 10 days in 12 healthy subjects (6 men and 6 women) . The second investigation included 2 studies . One was a DDI study using 2 CYP2D6 substrates (desipramine and metoprolol).…”
Section: Methodsmentioning
confidence: 99%
“…SIM‐desipramine and SV‐metoprolol compound models are available in Simcyp and were used without modification. The virtual population in Simcyp was designed to match the clinical study population as described previously . For the PBPK simulations in the CYP2D6 EM population in accordance with clinical design with CYP2D6 EM subjects, the Healthy Volunteer Population file was used by modifying the frequency of the CYP2D6 PM, intermediate‐metabolizer, and ultrarapid metabolizer phenotypes to 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation